Immune Dysregulation in Bipolar Disorder: The Role of IL-27 and EBI3 - Golnaz Sheykhnazari; Maliheh Ziaee; Ezinne Ijeoma Onuba; Najmeh Shahini; Yaser Bagheri (BJPsych Open)
Aims: Bipolar disorder (BD) is a severe psychiatric illness characterized by alternating depressive and manic episodes. The exact cause of BD remains unclear, but inflammatory and immunological processes are believed to play a significant role in its pathophysiology. Immune system dysregulation is a key factor, with pro-inflammatory markers like CRP, TNF-α, and IL-6 being elevated during mood episodes. Interleukin 27 (IL-27), which has both pro-inflammatory and anti-inflammatory properties, has not been extensively studied in BD. This study aims to investigate the levels of IL-27 and its subunit EBI3 in BD patients to better understand their role in the disease.